Birokrasi Pelayanan Publik di Kelurahan Talumolo Kecamatan Dumbo Raya Kota Gorontalo - Pricilia Ma’ruf; Mochammad Sakir; Hasan Bau (Fakultas Ilmu Sosial dan Ilmu Poliitik Universitas Ichsan Gorontalo, 2022)
This study aims to find out how the Public Service Bureaucracy in the Talumolo Village Office, Dumbo Raya District, Gorontalo City. This study uses service performance indicators concerning the opinion of Dwiyanto (2012: 50) namely: 1) Productivity, 2) Service Quality, 3) Responsiveness, 4) Responsibility, and 5) Accountability. The method used in this research is a qualitative approach with descriptive presentation. The informants in this study were seven people, five were employees of the Talumolo Village Office and two were the people of Talumolo Village. The data collection technique used in this research is using observation, interview, and documentation techniques. This study uses interactive data analysis techniques through data collection, data reduction, data presentation, and concluding. The results of the research on the Public Service Bureaucracy at the Talumolo Village Office, Gorontalo City, namely the productivity indicators, employee productivity at the Talumolo Village Office is still not good and still needs to be improved. The indicators of responsiveness and accountability of employees at the Talumolo sub-district office are classified as good, while the accountability indicators are still not good.